Edukasi Persyaratan Mikrobiologi Air Minum untuk Pelaku Usaha Depot Air Minum di Pariaman - Zaunit, Muthia Miranda; Yenti, Revi; Agusman, Agusman; Vatur, Kayla Maharani; Annisa, Sarah Dwi (Universitas Pahlawan Tuanku Tambusai, 2024)
The need for refill drinking water that is hygienic and in accordance with existing regulatory standards is very important for the community (consumers). There are still many Depot Air Minum (DAM) in Pariaman that do not meet the microbiological requirements of drinking water. Therefore, it is necessary to conduct a seminar on understanding the microbiological requirements of drinking water for DAM businesses in Pariaman. The seminar was conducted using lecture and discussion methods. The seminar was conducted on Saturday 28 September 2024, in the Meeting Room of RM Jembatan Sunua and was attended by 20 participants. The seminar began with giving a pre-test to the participants, followed by the presentation of material by four speakers: microbiological requirements for drinking water, depot licensing, coliform and UV sterilisation machines and the role of associations. In the discussion session, there were three questions from the participants which were immediately responded to by the speakers. After the discussion, participants were given a post test. From the evaluation of pre-test and post-test scores, there was an increase in participants' understanding of the microbiological requirements of drinking water from 63.5% to 87%. At the end of the event, the PKM team handed over five 12 GPM UV sterilisation machines to five lucky participants. It can be concluded that the seminar on microbiological requirements of drinking water can increase the understanding of DAM actors about the quality of drinking water sold.